KARAKTERISTIK FUNGSIONAL PROTEIN MISELIUM JAMUR TIRAM MERAH MUDA DAN MERANG [Functional Characteristics of Protein Mycelium of Pink Oyster and Paddy Straw Mushrooms] - - Sukarno; Nadia T. Hendartina; Dedi Fardiaz; Nampiah Sukarno (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
KARAKTERISTIK FUNGSIONAL PROTEIN MISELIUM JAMUR TIRAM MERAH MUDA DAN MERANG [Functional Characteristics of Protein Mycelium of Pink Oyster and Paddy Straw Mushrooms]Sukarno1)*, Nadia T. Hendartina1), Dedi Fardiaz1) dan Nampiah Sukarno2)1) Departemen Ilmu dan Teknologi Pangan, Fakultas Teknologi Pertanian, Institut Pertanian Bogor, Bogor2) Departemen Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Institut Pertanian Bogor, Bogor Diterima 12 Maret 2014 / Disetujui 13 Juni 2014ABSTRACT Mycelium of mushroom contained high protein, which determined its functional characteristics such as water holding capacity (WHC), oil holding capacity (OAC), emulsion stability, and gel formation. This study aimed to determine the protein functional properties of Pleurotus flabellatus and Volvariella volvacea mycelia. Information obtained can be used to increase utilization of the mycelia as source of food. Mycelia biomass were obtained by growing the fungal cultures in Potato Dextrose Broth (PDB) on shaker at 100-150 rpm. Mycelia were harvested three times at 7, 8, and 9-days after inoculation for measuring their protein contents by kjehdahl method. Functional properties of mycelium protein measured were WHC, OAC, emulsion stability, and gel formation by folding test method. Based on the analysis of protein content in dry weight basis, 8-day old P. flabellatus and V. volvacea mycelia produced the highest protein contents with the value were 31.72 and 19.98%, respectively. Further analysis of protein functional properties showed that P. flabellatus mycelium had 10.38% of WHC, 0.52 mL/g of OAC, 57.14% of emulsion stability and gel strength level with the valueof 2, whereas the V. volvacea mycelium had 15.89% of WHC, 0.80 mL/g of OAC, 48.69% of emulsion stability, and did not form a gel. Protein functional properties of P. flabellatus were better than that of V. volvacea mycelium in terms of protein content, emulsion stability, and gel formation.